PROBLEMS OF TRANSLATION OF STATIVE VERBS IN ENGLISH AND UZBEK LANGUAGES (Journal of Universal Science Research, 2025)
This article gives information about mental verbs and their role in the literature. In the Uzbek language, different variants of mental stative verbs such as “hadiksiramoq”, “qadrlamoq”, “magrurlanmoq”, “qanoatsizlanmoq” and “toqatsizlanmoq” are considered. Verbs such as “struggle”, “contemplate”, “conceive”, and “despise” in English have also been analyzed by considering that their semantics can be expressed in Uzbek through different verbs.